Impact of primary staging with fibroblast activation protein specific enzyme inhibitor (FAPI)-PET/CT on radio-oncologic treatment planning of patients with esophageal cancer - Ristau, Jonas; Giesel, Frederik L.; Häfner, Matthias; Staudinger, Fabian; Lindner, Thomas; Merkel, Andreas; Schlittenhardt, Joel; Kratochwil, Clemens; Choyke, P. L.; Herfarth, Klaus; Debus, Jürgen; Haberkorn, Uwe; et al. (Molecular imaging & biology, 2020)
Quinoline-based ligands targeting cancer-associated fibroblasts have emerged as promising radiopharmaceuticals in different tumor entities. The aim of this retrospective study was to explore the potential of FAPI-PET/CT in the initial staging of esophageal cancer patients and its usefulness in radiotherapy planning as a first clinical analysis.